2020
DOI: 10.3390/ijerph17165634
|View full text |Cite
|
Sign up to set email alerts
|

Winter Is Coming: A Southern Hemisphere Perspective of the Environmental Drivers of SARS-CoV-2 and the Potential Seasonality of COVID-19

Abstract: SARS-CoV-2 virus infections in humans were first reported in December 2019, the boreal winter. The resulting COVID-19 pandemic was declared by the WHO in March 2020. By July 2020, COVID-19 was present in 213 countries and territories, with over 12 million confirmed cases and over half a million attributed deaths. Knowledge of other viral respiratory diseases suggests that the transmission of SARS-CoV-2 could be modulated by seasonally varying environmental factors such as temperature and humidity. Many studies… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
89
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(96 citation statements)
references
References 201 publications
(305 reference statements)
1
89
0
1
Order By: Relevance
“…The copyright holder for this this version posted September 14, 2020. ; https://doi.org/10.1101/2020.09.12.20193250 doi: medRxiv preprint have already reported effects of environmental variables such as temperature, humidity, UV levels, and wind-speed on the transmission of SARS-CoV-2 [17][18][19][20][21][22][23][24] . While, in general, most studies appear to support increased transmission rates under cool, dry conditions 18 , conflicting results have been observed 21,25 and collectively the environmental signal appears to be weak 5 . Much of the variability in these early results is likely due to the use of inappropriate response variables (such as cases or fatalities) which fail to capture the intrinsic variations in transmission intensity driven by the effects of non-pharmaceutical intervention measures 5 .…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…The copyright holder for this this version posted September 14, 2020. ; https://doi.org/10.1101/2020.09.12.20193250 doi: medRxiv preprint have already reported effects of environmental variables such as temperature, humidity, UV levels, and wind-speed on the transmission of SARS-CoV-2 [17][18][19][20][21][22][23][24] . While, in general, most studies appear to support increased transmission rates under cool, dry conditions 18 , conflicting results have been observed 21,25 and collectively the environmental signal appears to be weak 5 . Much of the variability in these early results is likely due to the use of inappropriate response variables (such as cases or fatalities) which fail to capture the intrinsic variations in transmission intensity driven by the effects of non-pharmaceutical intervention measures 5 .…”
Section: Introductionmentioning
confidence: 96%
“…While, in general, most studies appear to support increased transmission rates under cool, dry conditions 18 , conflicting results have been observed 21,25 and collectively the environmental signal appears to be weak 5 . Much of the variability in these early results is likely due to the use of inappropriate response variables (such as cases or fatalities) which fail to capture the intrinsic variations in transmission intensity driven by the effects of non-pharmaceutical intervention measures 5 . Furthermore, COVID-19 has taken hold in many places with diverse climates and there are obvious examples of high transmission rates under hot, humid conditions, e.g.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Some of these studies have focused on specific regions and countries, such as 122 cities in China [10], Wuhan, China [11], Mainland China [12], Jakarta, Indonesia [13], India [14,15], Iran [16], Brazil [17], Europe and United States [18], and Russia [19], while others have examined the effect of weather conditions on the pandemic at a global scale . Smit et al [42], who presented a comprehensive critical review of the relevant literature published in the first half of 2020, concluded that it is important for studies to include the effects of socio-economic factors and non-pharmaceutical interventions (such as government response measures) in their analysis.…”
Section: Introductionmentioning
confidence: 99%
“…As Covid-19 raged all over the world and did not disappear in the summer months, only reduced seasonality can be expected. While [24] found that multiple meteorological aspects such as temperature, humidity, and wind speed influence the spread of the disease, the analysis of over 100 articles in [81] found only a "weak modulation effect" so far, with more evidence only to be expected in 2021. However, another important aspect of seasons is the transition from outdoor to indoor contacts.…”
Section: Influence Of the Seasonsmentioning
confidence: 99%